WOMEN'S DISCRIMINATION OF BEAUTY IS A WOUND: FEMINIST STYLISTICS APPROACH OF SARA MILLS - Lu'luil Maknun; Rimajon Sotlikova; Elysa Hartati (Literature and Literacy, 2023)
This study investigated woman discrimination by the theory of critical discourse analysis from Sara Mills perspective. Novel Beauty is a Wound by Kurniawan was the source of the research. The data were analyzed by qualitative descriptive technique through data reduction, data display, and conclusion drawing or verification employing the feminist literary criticism theory by revealing woman’ discrimination in the position of the subject, the object position, and the position of the reader. The findings and results of this study revealed that there were thirty data of female discrimination in the position of subject, seven of data female discrimination in the position of object and three data on discrimination against women in the position of the reader. Then, this study investigated and found five forms of discrimination against women, namely: (1) marginalization, (2) subordination of women (secondary), (3) female stereotypes (negative labeling), (4) violence against women (violence), (5) women's double workload. This study suggests some points, adults’ reader is encouraged to think openly and not to easily assign any kinds of woman discriminations to other, spread the woman empowerment spirit to others and unnormalize the kind of discrimination against women that are subconsciously recognized, accepted, and judged by other women as well.